Spatial Evolution of Sports Tourism Space: a case study of Shandong Province, China - Jun, Jiang; Fugao , Jiang (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
This study adopted the method of literature, mathematical statistics, logic analysis and GIS spatial analysis, taking the spatial elements of sports tourism in Shandong Province from 2009 to 2018 as the research object, clarified the development status of sports tourism in Shandong Province and the distribution status of spatial elements, sorted out the characteristics of the spatial evolution of sports tourism in Shandong Province, and analyzed the influencing factors of the spatial evolution of sports tourism in Shandong Province. To explore the countermeasures for the development of sports tourism in Shandong province and provide reference for enriching the research plan of sports tourism space in Shandong province and improving the theory of sports tourism space development. It provides empirical reference for optimizing the spatial layout of sports tourism development in Shandong province, balancing the seasonal imbalance of sports tourism in Shandong province, creating high-quality sports tourism brands in Shandong Province, and promoting the development of sports tourism in Shandong province